Development Prospects of National Creative Industry Through Islamic Films in Malaysia - Mansor, Nuruul Hidayah; Ayub, Mohamad Shafiei; Abdul Razak, Abdul Qayuum (Online Journal of Research in Islamic Studies, 2019)
Creative industry sector which contributes to the country's development of economy also offers opportunities for the local artists to further generate new ideas that are competitive for the international level. At the same time, the development that is brought by the creative industry has also produced a huge prospect to the programming and broadcasting services in Malaysia. With regard to this, the creations of new ideas in upholding the local creative industry through the making of Islamic films are among the initiatives that need to be supported by all bodies as this will also promote Islamic values and Islamic Malay cultures in Malaysia.